Phantom study of SPECT/CT augmented reality for intraoperative localization of sentinel lymph nodes in head and neck melanoma. (February 2022) - Nakamoto, Ryusuke; Zhuo, Jialin; Guja, Kip E.; Duan, Heying; Perkins, Stephanie L.; Leuze, Christoph; Daniel, Bruce L.; Franc, Benjamin Lewis
Highlights: Identification of sentinel lymph node (SLN) is critical for treating melanoma. An augmented reality (AR) headset allows surgeons to visualize SPECT/CT in 3D. The AR headset was useful for rapid detection of targets on head and neck phantoms. The AR headset may reduce the SLN detection time during head and neck surgery. Abstract: Objective: To show that augmented reality (AR) visualization of single-photon emission computed tomography (SPECT)/computed tomography (CT) data in 3D can be used to accurately localize targets in the head and neck region. Materials and methods: Eight head and neck styrofoam phantoms were painted with a mixture of radioactive solution (Tc-99m) detectable with a handheld gamma probe and fluorescent ink visible only under ultraviolet (UV) light to create 10–20 simulated lymph nodes on their surface. After obtaining SPECT/CT images of these phantoms, virtual renderings of the nodes were generated from the SPECT/CT data and displayed using a commercially available AR headset. For each of three physician evaluators, the time required to localize lymph node targets was recorded (1) using the gamma probe alone and (2) using the gamma probe while wearing the AR headset. In addition, the surface localization accuracy when using the AR headset was evaluated by measuring the misalignment between the locations visually marked by the evaluators and the ground truth locations identified using UV stimulation of the ink at the site of the nodes. Results: For all three evaluators, using the AR headset significantly reduced the time to detect targets ( P = 0.012, respectively) compared to using the gamma probe alone. The average misalignment between the location marked by the evaluators and the ground truth location was 8.6 mm. Conclusion: AR visualization of SPECT/CT data in 3D allows for accurate localization of targets in the head and neck region, and may reduce the localization time of targets.